2007
DOI: 10.1116/1.2713406
|View full text |Cite
|
Sign up to set email alerts
|

Fast neutron irradiation effects in n-GaN

Abstract: Impact of deep levels on the electrical conductivity and luminescence of gallium nitride codoped with carbon and silicon J. Appl. Phys. 98, 053704 (2005); 10.1063/1.2005379 A method to determine deep level profiles in highly compensated, wide band gap semiconductors J. Appl. Phys. 97, 083529 (2005); 10.1063/1.1862321 Neutron irradiation effect on radio-frequency magnetron-sputtered GaN thin films and Au/GaN Schottky diodes The electrical properties and deep level spectra in undoped n-GaN films irradiated by fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 30 publications
1
65
0
Order By: Relevance
“…Due to these induced defects, trapping centers are created, and the Fermi level is pinned within the energy levels of these defects. For example, Polyakov et al 117 found that under a high neutron fluence of $10…”
Section: à2mentioning
confidence: 99%
“…Due to these induced defects, trapping centers are created, and the Fermi level is pinned within the energy levels of these defects. For example, Polyakov et al 117 found that under a high neutron fluence of $10…”
Section: à2mentioning
confidence: 99%
“…With rare exceptions, only for higher electron energies [11], heavier ions (He, N) [15,19], neutron irradiation [20] or higher density of defects in proton implanted samples (as for 150 keV protons with the dose over 5×10 14 cm -2 [21]) are deeper traps commonly detected. Electron traps that are generally observed in these cases show the activation energies of 0.75-0.8 eV, 0.95-1.2 eV [11,15,[19][20][21]. The 0.8 eV traps show decrease of the ionization energy with increasing electric fi eld whereas the 1 eV traps energy does not vary with electric fi eld.…”
Section: Levels Of Radiation Defects In Ganmentioning
confidence: 99%
“…The fi rst type of behavior is expected for donors because of the PooleFrenkel effect [22], whilst the second type of behavior is characteristic of acceptors that are neutral when they emit an electron [22]. The attribution based mostly on theoretical calculations tends to ascribe the fi rst to Ga i 2+ deep donors and the second to N i 2+ deep acceptors [9,11,15,20]. In addition to these deep centers, implantation of n-GaN with 150 keV protons to doses higher than 5×10 14 cm -2 creates deep electron traps whose energies increased from 0.2 eV at low dose to 0.25 eV, 0.32 eV and 0.45 eV at higher dose suggesting that these centers could be larger complexes produced by addition of new radiation defects to the more simple radiation defects formed at low doses [21].…”
Section: Levels Of Radiation Defects In Ganmentioning
confidence: 99%
See 1 more Smart Citation
“…The main degradation mechanisms such as the current collapse, the permanent increased leakage current, and the instable threshold voltage, are considered to associate with the trapping effect for AlGaN/GaN MIS-HEMTs [2][3][4][5][6]. Deep level Transient Spectroscopy (DLTS) is used to analyse the deep level defects in AlGaN/GaN MIS-HEMTs [7][8][9][10]. However, for a DLTS test, a well-controlled temperature cabinet with a wide temperature scope (dozens of K to hundreds of K) is required.…”
Section: Introductionmentioning
confidence: 99%